IMPLEMENTASI PROBLEM-BASED LEARNING BERBANTUAN ICT UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMK - Wati Ariyanti; Asep Ikin Sugandi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This is the classroom action research which aims to determine the improvement of the mathematical understanding ability of  XI-class students, through the problem-based learning method assisted by ICT. The subjects in this study were XI AKL 1 students of  SMKN 11 Bandung, which involved 24 students. This classroom action research consists of 3 cycles, namely cycles I – III with 2 meetings each. The instrument used in data collection is the results of LKPD 1-3. Techniques in presentation data using descriptive tables in the form of averages and percentages. The study results indicate Problem-Based Learning  implementation can gain students' mathematical understanding ability. The first cycle progress is specified by the increase in learning outcomes  with the score average of  68, showing 54%. It is followed by  the second cycle which shows the score average of 80 with 75%. Furthermore, the third cycle releases the score average of 81 with 79%.